Flow Rate Control by Means of Flow Meter and PLC Controller - Sylwia Włodarczak; Marek Ochowiak; Michał Doligalski; Bartosz Kwapisz; Andżelika Krupińska; Marcin Mrugalski; Magdalena Matuszak (Sensors, 2021)
This paper presents a design of a flow meter based on a programmable logic controller (PLC). The new construction of a flow meter controlled by PLC increases the possibilities for the control and automation of fluid flow. Additionally, the didactic potential of the use of simple automation in the form of a programmable logic controller was considered. A device enabling the measurement of fluid flow rate based on a PLC controller was designed, constructed, and tested. The choice of device was the Gems Sensors FT-210 series turbine flow sensor, which is characterized by low purchase and maintenance costs. The properties and the chemical resistance of polyamide-12, the material the sensor is made of, make it possible to test the flow of various types of fluids. As part of the work, an algorithm and a program controlling the device was developed based on the APB Soft software, enabling the accurate reading of the number of impulses sent by the turbine flow sensor. The results of the designed flow meter were compared with the results obtained for the Krohne VA-40 high accuracy rotameter.